Cyanobacterial water bloom of Limnoraphis robusta in the Lago Mayor of Lake Titicaca. Can it develop? - Komarkova, J (2016)
This study was realized under the support of the bilateral international collaboration between the Czech Academy of Sciences and CONCYTEC (Peru) 2013-2014. We thank Dr. Gertrud Cronberg, Institute of Limnology, Lund, Sweden, for offering us her unpublished data about the composition of phytoplankton of the Atitlan and Amatitlan lakes from the year 1983. We are indebted to our referees both for comments on the text and helpful cultivation of our English.